2022
DOI: 10.3390/microorganisms10112283
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Genomic Diversity among Carbapenem-Resistant Escherichia coli Clinical Isolates and Antibacterial Efficacy of Silver Nanoparticles from Pakistan

Abstract: The emergence of carbapenem-resistant Escherichia coli (E. coli) is considered an important threat to public health resulting in resistance accumulation due to antibiotics misuse and selection pressure. This warrants periodic efforts to investigate and develop strategies for infection control. A total of 184 carbapenem-resistant clinical strains of E. coli were characterized for resistance pattern, resistance genes, plasmids, sequence types and in vitro efficacy of silver nanoparticles (AgNPs). Carbapenem resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…as main producer species. Other reports from Pakistan supplement our findings that K. pneumoniae and E. coli were major contributors of the total carbapenemase production among Enterobacterales [ 15 , 17 , 40 , 44 , 57 , 90 , 91 ]. Another study observed a high proportion of carbapenemase production among Citrobacter spp.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…as main producer species. Other reports from Pakistan supplement our findings that K. pneumoniae and E. coli were major contributors of the total carbapenemase production among Enterobacterales [ 15 , 17 , 40 , 44 , 57 , 90 , 91 ]. Another study observed a high proportion of carbapenemase production among Citrobacter spp.…”
Section: Discussionsupporting
confidence: 88%
“…The key contributing carbapenemases involved in the expansion of CPE in the study population are bla NDM-1 and bla OXA-48 , confirming the existing data from Pakistan [ 14 , 15 , 17 , 40 , 45 , 57 , 90 , 91 , 92 ]. We observed a considerable increase in the prevalence of KPC-producing K. pneumoniae (15.4%).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Recently, several reports have demonstrated the dissemination of bla NDM encoding gene among E. coli isolated from patients in various geographical locations [ 7 ]. The heterogenicity of the genetic environment of bla NDM encoding gene, combined with its location on plasmids of different incompatibility groups (Inc) has led to the emergence of diverse CREC clones worldwide [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%